2011
DOI: 10.1016/j.yexmp.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Absence of galectin-3 does not affect the development of experimental tongue carcinomas in mice

Abstract: Absence of galectin-3 did not directly affect the process of carcinogenesis and a cytoplasm shift of galectin-3 seems to be associated with development of tongue carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
1
5
0
6
Order By: Relevance
“…In contrast, Eude-Le Parco et al (2009) showed no influence of Gal3 in the development of breast and colon tumors or in the occurrence of metastasis in LGALS3-silenced mice. Similarly, our previous report found no difference in the incidence of tongue tumor between Gal3 +/+ and Gal3−/− mice, which in part might be associated with equal and persistent Wnt signaling pathway activation in both genotypes (de Faria et al, 2011;Sant'ana et al, 2011). This observation was confirmed herein, because Wnt3 expression, an important activator of this pathway, was similarly expressed in all dysplasia and carcinoma samples from both genotypes.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In contrast, Eude-Le Parco et al (2009) showed no influence of Gal3 in the development of breast and colon tumors or in the occurrence of metastasis in LGALS3-silenced mice. Similarly, our previous report found no difference in the incidence of tongue tumor between Gal3 +/+ and Gal3−/− mice, which in part might be associated with equal and persistent Wnt signaling pathway activation in both genotypes (de Faria et al, 2011;Sant'ana et al, 2011). This observation was confirmed herein, because Wnt3 expression, an important activator of this pathway, was similarly expressed in all dysplasia and carcinoma samples from both genotypes.…”
Section: Discussionsupporting
confidence: 58%
“…The findings on 4NQO-induced tongue carcinogenesis in Gal3+/+ and Gal3 −/− mice have previously been published elsewhere (de Faria et al, 2011).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“… showed that the absence of galectin‐3 does not directly present a role in the oral carcinogenesis after chemical treatment in mice. Despite these contradictory results, the level of galectin‐3 expression seems to depend on the type of tissue studied, a fact suggesting that specific tumor factors modulate the expression of this protein .…”
Section: Discussionmentioning
confidence: 98%
“…Treatment with the carcinogen 4NQO (Sigma, St. Louis, MO, USA) followed the protocol described by Faria, Chammas, Melo et al (2011). This protocol consist in dilute the 4NQO in filtered water until it attained the concentration of 100 µg/ ml.…”
Section: Experimentation Protocolmentioning
confidence: 99%